Maintenance of protective immunity against malaria by persistent hepatic parasites derived from irradiated sporozoites. - Scheller, L F (1995)
Immunization of rodents and humans with irradiation-attenuated malaria sporozoites confers preerythrocytic stage-specific protective immunity to challenge infection. This immunity is directed against intrahepatic parasites and involves T cells and interferon gamma, which prevent development of exoerythrocytic stages and subsequent blood infection. The present study was undertaken to determine how protective immunity is achieved after immunization of rodent hosts with irradiated Plasmodium berghei sporozoites. We present evidence that irradiated parasites persist in hepatocytes of rats and mice for up to 6 months after immunization. A relationship between the persistence of parasites and the maintenance of protective immunity was observed. Protective immunity was abrogated in irradiated-sporozoite-immunized rats following the application of chemotherapy to remove preexisting liver parasites. Additionally, protective immunity against sporozoite challenge was established in rats vaccinated with early and late hepatic stages of irradiated parasites. These results show that irradiation-attenuated sporozoites produce persistent intrahepatic stages in vivo necessary for the induction and maintenance of protective immunity.